Conceptual core design of the molten metal fueled microreactor with self-regulating capability. (August 2022) - Fei, T.; Mo, K.; Miao, Y.; Forsyth, C.; Hu, R.; Bhattacharya, S.; Kim, T.
Highlights: Conceptual investigation of a stationary molten UMn fuel microreactor. Self-regulation capability due to high negative reactivity feedback and passive cooling. 3D Multiphysics coupling simulation for the reactor core under steady state and transient condition. Radial power flattening strategy. Abstract: The microreactor concept has received significant attention in the United States for its lower capital investment, siting flexibility and high mobility. A microreactor aims to provide reliable electricity in remote communities, mining areas, or isolated islands, which will save the high fuel transportation cost. Thus, minimizing the staff level for operating and maintaining a microreactor is desirable. The objective of the study is to design a self-regulated Molten Metal fueled microReactor core (MMR) and to demonstrate the self-regulating capability of the MMR core. The control of the reactor is solely relying on reactivity feedbacks from fuel temperature perturbation. Molten UMn (liquid form at the temperature over 720 °C) was utilized as the fuel material in MMR due to the larger thermal expansion coefficient compared to the conventional solid fuel. The MMR core has a fast neutron spectrum, which corresponds to a small burnup reactivity swing. The core design parameters were selected based on DAKOTA, REBUS, and ANLHTP calculations. The MMR is designed to run for 10 years at a power level of 15 MWth. No refueling is needed during the reactor lifetime. The system dynamic analyses were performed, and it was found that the reactor can be self-regulating within a temperature range of 800 ± 80 °C for a loss of heat sink transient.